Case Report: Persistent Moderate-to-Severe Creatine Kinase Enzyme Activity Elevation in a Subclinical Dog - Gunther, Melissa; Jaffey, Jared A.; Evans, Jason; Paige, Christopher (Frontiers in Veterinary Science, 2021)
A 4-year-old, male neutered, mixed breed dog was presented for a routine wellness examination at which time a moderatesevere increase in serum creatine kinase (CK) enzyme activity (hyperCKemia) (15,137 IU/L; reference interval 10-200 IU/L), and moderate increases in alanine transaminase and aspartate aminotransferase enzyme activities were first identified. There was no history of clinical abnormalities (e.g., lethargy, lameness, anorexia, dysphagia, weakness, gait abnormalities, or exercise intolerance) and the physical examination was unremarkable. The dog was screened for several relevant potential infectious diseases known to cause inflammatory myopathies and was treated empirically with clindamycin. after all infectious disease testing results were negative. The serum total CK enzyme activity remained severely increased, which prompted recommendations for an echocardiogram, electromyogram (EMG), and muscle biopsy acquisition. The echocardiogram and electrocardiographic monitoring were unremarkable. The EMG and muscle biopsies were declined by the owner. The dog was evaluated several times in the subsequent 5 years and remained subclinical with unremarkable physical examinations despite a persistent moderate-to-severe hyperCKemia. Differential diagnoses considered most likely in this dog were an occult/latent hereditary muscular dystrophic disorder or idiopathic hyperCKemia, a phenomenon not yet reported in the veterinary literature. This report describes for the first time, clinical and diagnostic features of a subclinical dog with persistent moderate-to-severe hyperCKemia.